Ethical aspects for genomic research in psychiatry - N. V. Semenova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The genomic research is one of the most dynamically developing fields both in the worldwide and in Russia. Currently, the genetic approaches in psychiatry are used to solve the practical and scientific problems related to medical genetic counseling, identification of the genetic factors associated with characteristics of metabolism of medicines or development of their side effects, as well as to develop the new approaches to classification of psychiatric disorders. Given the complexity and the unresolved nature of the several methodological issues related to ethics and protection of the rights of patients with mental disorders, the legal regulation of genomic research in this category of patients is a specific interdisciplinary challenge which solution requires combining of the competencies of lawyers, medical ethics specialists, psychiatrists, psychologists, geneticists.